Antibiotic Resistance of Escherichia coli Serotypes from Cochin Estuary - Divya P. Sukumaran; Srinivasan Durairaj; Mohamed Hatha Abdulla (Interdisciplinary Perspectives on Infectious Diseases)
This study aimed at detecting the prevalence of antibiotic-resistant serotypes of Escherichia coli in Cochin estuary, India. E. coli strains were isolated during the period January 2010–December 2011 from five different stations set at Cochin estuary. Water samples from five different stations in Cochin estuary were collected on a monthly basis for a period of two years. Isolates were serotyped, antibiogram-phenotyped for twelve antimicrobial agents, and genotyped by polymerase chain reaction for uid gene that codes for β-D-glucuronidase. These E. coli strains from Cochin estuary were tested against twelve antibiotics to determine the prevalence of multiple antibiotic resistance among them. The results revealed that more than 53.33% of the isolates were multiple antibiotic resistant. Thirteen isolates showed resistance to sulphonamides and two of them contained the sul 1 gene. Class 1 integrons were detected in two E. coli strains which were resistant to more than seven antibiotics. In the present study, O serotyping, antibiotic sensitivity, and polymerase chain reaction were employed with the purpose of establishing the present distribution of multiple antibiotic-resistant serotypes, associated with E. coli isolated from different parts of Cochin estuary.